Enriching the Pore: Splendid Complexity from Humble Origins. (8th January 2014) - Field, Mark C.; Koreny, Ludek; Rout, Michael P.
Abstract The nucleus is the defining intracellular organelle of eukaryotic cells and represents a major structural innovation that differentiates the eukaryotic and prokaryotic cellular form. The presence of a nuclear envelope (NE) encapsulating the nucleus necessitates a mechanism for interchange between the contents of the nuclear interior and the cytoplasm, which is mediated via the nuclear pore complex (NPC), a large protein assembly residing in nuclear pores in the NE. Recent advances have begun to map the structure and functions of the NPC in multiple organisms, and to allow reconstruction of some of the evolutionary events that underpin the modern NPC form, highlighting common and differential NPC features across the eukaryotes. Here we discuss some of these advances and the questions being pursued, consider how the evolution of the NPC has been constrained, and finally propose a model for how the NPC evolved. <inline-graphic xlink:href="ark:/27927/pgg409t85qw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />